Biobehavioral Responses of Preterm Infants to Conventional and Swaddled Tub Baths: A Randomized Crossover Trial. Issue 4 (October 2018) - de Freitas, Patrícia; Bueno, Mariana; Holditch-Davis, Diane; Santos, Hudson Pires; Kimura, Amélia Fumiko
Abstract : Bathing is a routine care procedure that exposes preterm infants to prolonged handling, which could cause stress and potentially disrupt infants' biobehavioral responses. The aim of this double-blind randomized crossover trial was to compare the preterm infant's body temperature, heart rate (HR), peripheral capillary oxygen saturation (SpO2 ), salivary cortisol levels, and sleep-wake states during and after swaddled and conventional tub baths. Forty-three infants born at 32 to 36 weeks postmenstrual age, weighing 2225 g or less, were enrolled in the study. Infants were videotaped before and after each type of baths. The time interval between baths ranged from 24 to 72 hours to allow a washout period. Physiological, hormonal, and behavioral responses were collected at baseline and during recovery from baths. No significant differences in the mean body temperature, HR, SpO2, salivary cortisol levels, and sleep-wake states between the bath types were observed in the baseline or recovery responses during the first 20 minutes after bath. Regardless of bath type, salivary cortisol levels showed a nonstatistical significant increase.